2019
DOI: 10.3390/electronics8070794
|View full text |Cite
|
Sign up to set email alerts
|

Expressing Personalities of Conversational Agents through Visual and Verbal Feedback

Abstract: As the uses of conversational agents increase, the affective and social abilities of agents become important with their functional abilities. Agents that lack affective abilities could frustrate users during interaction. This study applied personality to implement the natural feedback of conversational agents referring to the concept of affective computing. Two types of feedback were used to express conversational agents' personality: (1) visual feedback and (2) verbal cues. For visual feedback, participants (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…The first study showed that, as the uses of conversational agents increase, the affective and social abilities of agents become as important as their functional abilities in the open innovation engineering channel and system dynamics approaches [55]. Consequently, by building networks to harness innovation synergies, open system approaches can motivate sustainable development and creative collaboration based on both online and offline learning systems [56,57].…”
Section: Editorial Of Soi 2019 Special Issue Of Electronicsmentioning
confidence: 99%
“…The first study showed that, as the uses of conversational agents increase, the affective and social abilities of agents become as important as their functional abilities in the open innovation engineering channel and system dynamics approaches [55]. Consequently, by building networks to harness innovation synergies, open system approaches can motivate sustainable development and creative collaboration based on both online and offline learning systems [56,57].…”
Section: Editorial Of Soi 2019 Special Issue Of Electronicsmentioning
confidence: 99%
“…People are more engaged in interacting with others who have similar personality profiles as it requires less information processing and cognitive load (Wu et al, 2017). This idea has been used in designing dialog systems and personal assistants emphasising the need for them to be able to detect and mimic the personality style of a user (Cassell and Bickmore, 2003;Ma et al, 2019;Seo-young Lee and Lee, 2019), in order to behave similarly to humans that instinctively adapt to the other person's personality (Funder and Sneed, 1993;McLarney-Vesotski et al, 2006). It has been shown that adding personality traits to virtual agents leads to significantly better perceived emotional intelligence of such systems (Ma et al, 2019).…”
Section: Use Of Personality Detection In Nlp Applicationsmentioning
confidence: 99%
“…Also, disfluency in speech and fillers [46] portray a less conscientious CA. Slow speed and high emotionality [47] in voice are found to have a correlation with high conscientiousness -however, this only applies to the female voice [47].…”
Section: Reviewing Abstractsmentioning
confidence: 84%
“…Databases: Scopus ACM Digital Library controlled body movements [22] reflect a high score in openness when it comes to an ECA's body language, the studies did not contain any further information on the trait's opposite pole. In the category paraverbal language, research showed that disfluencies in speech [46] is characteristic for low openness, while high emotionality in female voice [47] is considered a personality cue for high openness. We did not find any cues regarding verbal language.…”
Section: Reviewing Abstractsmentioning
confidence: 99%
See 1 more Smart Citation